2021
DOI: 10.3390/cancers13205231
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Shorter p53 Family Isoforms Can Impact Melanoma Aggressiveness

Abstract: Cutaneous melanoma is the most aggressive form of skin cancer. Despite the significant advances in the management of melanoma in recent decades, it still represents a challenge for clinicians. The TP53 gene, the guardian of the genome, which is altered in more than 50% of human cancers, is rarely mutated in melanoma. More recently, researchers started to appreciate the importance of shorter p53 isoforms as potential modifiers of the p53-dependent responses. We analyzed the expression of p53 and p73 isoforms bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 72 publications
(105 reference statements)
1
29
0
Order By: Relevance
“…This may explain why p53β-positive staining was found in both cellular compartments in this study. Both Δ133p53α and Δ160p53α have been described to localise in the nucleus with minor staining in the cytoplasm; however, Δ160p53α can also present peri nucleolar localisation [ 4 , 5 , 40 ]. This indicates that these isoforms may be travelling between the cytoplasm and the nucleus; however, isoform translocation within cellular compartments could depend on the cellular context (e.g., in response to DNA damage).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why p53β-positive staining was found in both cellular compartments in this study. Both Δ133p53α and Δ160p53α have been described to localise in the nucleus with minor staining in the cytoplasm; however, Δ160p53α can also present peri nucleolar localisation [ 4 , 5 , 40 ]. This indicates that these isoforms may be travelling between the cytoplasm and the nucleus; however, isoform translocation within cellular compartments could depend on the cellular context (e.g., in response to DNA damage).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid vectors for full-length wild-type p53 (pRcCMV-p53WT) were generously provided by Prof. Helen Rizos (Department of Biomedical Sciences, Macquarie University, Sydney, Australia). The constructs for p53β (pSV40-p53β), Δ133p53 (pSV40133-p53), Δ160p53 (pCDNA3.1-Δ160p53α) and the control vector pSV40 were kindly provided by Dr. Jean-Christophe Bourdon (Cellular Medicine, School of Medicine, The University of Dundee, Dundee, Scotland, UK) and have been previously described [ 4 , 12 , 40 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the controlled modulation of the expression pattern of p53 isoforms, by antisense oligonucleotides at the RNA level [ 53 , 57 ], and by small molecules at the protein level [ 68 ], which could be an alternative approach in anti-cancer therapy applied in RCC in the future. Moreover, monitoring of changes in expression profiles of the specific isoforms including p53β, p53γ, Δ133p53, and Δ160p53 might be applied in a personalized medicine to increase therapy effectiveness [ 33 , 63 , 65 ]. Altogether, p53 and its isoforms seem to mediate cell response and cell sensitivity to treatment in renal cell carcinoma; however, more research is needed to better understand the role of network interactions between p53 and its isoforms with other proteins and RNAs in this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the Δ133p53 protein is engaged in carcinogenesis, including angiogenesis and metastasis, as well as in cellular events, including proliferation, cellular senescence, and apoptosis [ 56 , 60 , 61 ]. The Δ160p53 isoform’s second protein product, which is synthesized from a P2-initiated transcript, has been detected in several cell lines endogenously expressing different mutant p53s [ 62 , 63 ]. Moreover, wild-type p53 cell lines (HCT116, U2OS, and A549) show either no signs or low levels of Δ160p53 expression [ 64 ].…”
Section: P53 Isoforms In Rccmentioning
confidence: 99%
See 1 more Smart Citation